Practical Application of the New Approach To FMEA Method according to AIAG and VDA Reference Manual - Dariusz Plinta; Ewa Golinska; Ľuboslav Dulina (Communications - Scientific letters of the University of Zilina, 2021)
System requirements in the automotive industry are constantly evolving and being improved. Currently, the entire supply chain, related to the automotive industry, is subject to the fourth amendment to the technical automotive standard - IATF 16949: 2016 Quality management systems - Detailed requirements for the use of ISO 9001: 2015 in serial production and production of spare parts in the automotive industry. In IATF standard, there are advices called reference manuals that provide important guidance on the quality system in this industry - one of them is the FMEA manual. The new guidelines in this regard, developed jointly by AIAG and VDA, entered into force in June 2019. Presentation of the most important changes introduced, as well as presentation of a practical example of the conducted analysis is the purpose of the article.